2016
DOI: 10.1186/s12891-016-0982-2
|View full text |Cite
|
Sign up to set email alerts
|

Does hemipelvis structure and position influence acetabulum orientation?

Abstract: BackgroundAlthough acetabulum orientation is well established anatomically and radiographically, its relation to the innominate bone has rarely been addressed. If explored, it could open the discussion on patomechanisms of such complex disorders as femoroacetabular impingement (FAI). We therefore evaluated the influence of pelvic bone position and structure on acetabular spatial orientation. We describe this relation and its clinical implications.MethodsThis retrospective study was based on computed tomography… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“…Our measurements were performed using an original method of evaluation based on 3D CT reconstruction, a precise measurement tool whose reliability has been confirmed by previous studies (Jóźwiak et al, 2015; Musielak et al, 2016) as well as by high ICC values for intra- and inter-rater reliability. Geometric morphometric analysis was also carried out on 3D CT pelvis reconstructions using the Thin Plate Spline function, which enabled the interpolation of semilandmarks between the template and each sample.…”
Section: Discussionmentioning
confidence: 59%
See 2 more Smart Citations
“…Our measurements were performed using an original method of evaluation based on 3D CT reconstruction, a precise measurement tool whose reliability has been confirmed by previous studies (Jóźwiak et al, 2015; Musielak et al, 2016) as well as by high ICC values for intra- and inter-rater reliability. Geometric morphometric analysis was also carried out on 3D CT pelvis reconstructions using the Thin Plate Spline function, which enabled the interpolation of semilandmarks between the template and each sample.…”
Section: Discussionmentioning
confidence: 59%
“…We therefore considered it appropriate to define and precisely measure these distances to obtain high-quality results. All of the above-mentioned parameters were used recently by Musielak et al (2016) to evaluate the intrinsic relationship between the structures and positions of the pelvis and acetabulum.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The results showed that both measurements had good reliability for one observer and between observers, and simultaneously using the IWAA and the AWDI has good predictive value for the AAA. Similar to this study, Musielak et al 32 used the iliac opening angle to indicate the opening direction of the hemipelvis in the horizontal plane, but the morphological analysis of the open angle of the ilium for the acetabulum part of the hemipelvis was insufficient. Fuji et al 33 also analyzed the rotation of the ilium on three levels, but his measurement method failed to analyze the influence of the development of the anterior and posterior walls of the acetabulum on the acetabular opening.…”
Section: Discussionmentioning
confidence: 82%
“…This suggests that acetabular retroversion in Perthes disease may be caused by hemipelvic retroversion. Musielak et al 32 also found that the structure of the hemipelvis is closely related to the direction of the acetabulum, and the acetabulum will also be rotated back in proportion when the hemipelvis is rotated back in the horizontal plane. In this study, the AAA of the affected side of the case group was smaller than that of the contralateral side, and the IWAA of the affected side was smaller than that of the contralateral side.…”
Section: Discussionmentioning
confidence: 97%